Energy Performance Investigation Of Ethiopia Tannery Share Company - Salilish, Fekadu (ASTU, 2024)
In This Time Of Energy Crisis And Competitive Market, Company Should Be Able To Manage Electrical And Thermal Energy Inputs To Their Systems To Be Productive Locally And Internationally. One Way To Ensure Productivity Through Energy Management Is To Identify Energy Performances Of Various Equipment In Operation And Determine Energy Consumption Per Products Of Each System. An Energy Performance Investigation Has Been Conducted On Ethiopia Tannery S.C. The Major Purpose Of The Study Is To Find The Company??S Major Energy Consuming Systems And The Corresponding Energy Performance Through Data Collection And Analysis. Both Thermal And Electrical Energy Analysis Were Conducted Using A Number Of Data Collected And Analyzed Using System??S Online And Portable Instruments. Analysis Of Energy BillsFor The Past Years Of Both Fuel And Electricity Has Been Done, And Is Bench Marked With European Tanneries. The Major Energy Consuming System Of The Company Were Identified To BeBoiler, Steam Distribution System, Water Pumps, Electrical Motors And Lighting Systems. The Average Energy Consumption Per Meter Square Of Leather Is Found To Be 16.4 Kwh/M2 While The Minimum Average Is 5.1 Kwh/M2 And The Maximum Is 9.4 Kwh/M2, The Result Of The Bench Mark Needs Further Study Of The Process Of Leather Production. The Various Thermal Ener
Keywords: Energy Management, Energy Efficiency, Energy Analysist, Energy Conservation